Generational differences in payment habits and solutions in the digital space - Csiszárik, Viktor; Varga, János (Edelweiss Applied Science and Technology, 2024)
With the rise of digitalisation, payment habits and solutions have undergone a significant transformation, which is also driven by generational differences. Our study aims to explore how the payment preferences and habits of each generation differ in the digital space. Older generations tend to prefer more conservative payment methods, such as credit cards or cash, while younger generations are more open to modern, innovative solutions such as mobile payments and cryptocurrencies. Our paper highlights the extent to which technological developments and digital literacy are influencing the payment habits of different generations, and how the role of security and convenience is shaping the payment choices of different age groups. The study focuses on the financial literacy of each generation, including how to navigate 21st century finance. It is no exaggeration to say that not everyone has the same knowledge or understanding of modern finance. However, effective financial decision-making requires not only an understanding of traditional finance, but also the ability to keep abreast of the financial changes of the modern age. This study will hopefully shed light on the importance of the subject and the importance of developing financial literacy. We can strongly assume that financial literacy can be characterised at very different levels when looking at different generations, so it seems worthwhile to look more closely at the level of financial literacy among different generations. However, the present study focuses on financial habits and solutions.